Kontektualisasi Fakta Hukum ke dalam Ruang Kelas Digital: Sebuah Pengalaman Fakultas Hukum Universitas Negeri Semarang: Contextualization of Legal Facts into a Digital Classroom: An Experience of the Faculty of Law, State University of Semarang - Arifin, Ridwan (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The Covid-19 pandemic has encouraged the digitization of all aspects, including aspects of education and the learning process. Higher Education in Law also organizes online learning processes, both in theoretical and practical courses. In some cases, online learning has a positive impact, for example encouraging students and lecturers to explore the digital world optimally for various interests. On the other hand, several studies have proven that there is a learning gap in the online learning process. This paper aims to analyze how law students contextualize legal facts in digital classrooms. This study involved 300 students in six different classes (three classes of Criminology and Victimology, and three classes of Legal Aid Proficiency) at the Faculty of Law, State University of Semarang.